Feasibility and practical limits of full decarbonization of the electricity market with renewable energy: Application to the Spanish power sector. (15th January 2022) - Bonilla, Javier; Blanco, Julian; Zarza, Eduardo; Alarcón-Padilla, Diego C.
Abstract: Electricity market decarbonization using renewable energies is essential to significantly reduce greenhouse gas emissions. However, the identification of the optimum electrical mix for each country is a challenging and complex task because of the many boundary conditions that must be taken into account, thus demanding the use of advanced analysis and computing tools. This paper presents a methodology based on artificial intelligence developed for this purpose and the results obtained when applied to the specific case of the Spanish electricity market long-term decarbonization. It also shows how effective this methodology is to find the optimum electrical mix fulfilling previously defined objectives: 100% coverage of the demand while simultaneously minimizing the electricity cost and curtailments. Results show the significant barriers to achieve a 100% renewable electrical mix without excessive curtailments or installed power. The methodology described here is suitable for any other country and target objectives. Highlights: Smart electricity mix optimization based on artificial intelligence. Multi-objective optimization to simultaneously minimize cost and curtailments. The optimized mix covers the demand without exceeding the maximum greenhouse gas emissions. Application to the long-term full decarbonization of the Spanish power generation.